Redefining rapid reviews: a flexible framework for restricted systematic reviews - Plüddemann, A; Aronson, J; Onakpoya, I; Heneghan, C; Mahtani, K (BMJ Publishing Group, 2018)
Having suggested that so-called ‘rapid’ reviews have been misnamed and should instead be called ‘restricted reviews’, Members of the Oxford Centre for Evidence Based Medicine now suggest ways in which such reviews should be restricted.